Activation of percarbonate by water treatment sludge–derived biochar for the remediation of PAH-contaminated sediments. (October 2020) - Hung, Chang-Mao; Huang, Chin-Pao; Chen, Chiu-Wen; Wu, Chung-Hsin; Lin, Yi-Li; Dong, Cheng-Di
Abstract: Sludge from a groundwater treatment plant was used to prepare biochar by pyrolysis. The Fe–Mn rich biochar was used to activate percarbonate for the remediation of polycyclic aromatic hydrocarbons (PAHs) contaminated aquatic sediments. Results showed that the sludge–derived biochar (SBC) produced at a pyrolysis temperature of 700 °C was the most effective in activating percarbonate, which exhibited significant oxidative removal of PAHs. PAHs degradation took place via a Fenton-like oxidation manners, contributed from the Fe 3+ /Fe 2+ and Mn 3+ /Mn 2+ redox pairs, and achieved the highest degradation efficiency of 87% at pH0 6.0. Reactions between oxygenated functional groups of biochar and H2 O2 generated of O2 – and HO radicals in abundance under neutral and alkaline pH was responsible for the catalytic degradation of PAHs. Our results provided new insights into the environmental applications of SBC for the green sustainable remediation of organics-contaminated sediments and aided in reduction of associated environmental and health risk. Graphical abstract: Image 1 Highlights: Water treatment sludge was pyrolyzed to produce biochar (SBC). Percarbonate, activated by SBC, effectively degraded polycyclic aromatic hydrocarbons. Percarbonate activation enhanced the generation of reactive oxygen species. PAH degradation efficiency was affected by pyrolysis temperature, pH, and SBC dose. Langmuir-Hinshelwood model described the kinetics of PAH degradation well.